Content and discontent: a qualitative exploration of obstacles to elearning engagement in medical students. Issue 1 (December 2016) - Reid, Helen; Thomson, Clare; McGlade, Kieran
Abstract Background Elearning is ubiquitous in healthcare professions education. Its equivalence to 'traditional' educational delivery methods is well established. There is a research imperative to clarifywhen andhow to use elearning most effectively to mitigate the potential of it becoming merely a 'disruptive technology.' Research has begun to broadly identify challenges encountered by elearning users. In this study, we explore in depth the perceived obstacles to elearning engagement amongst medical students. Sensitising concepts of achievement emotions and the cognitive demands of multi-tasking highlight why students' deeply emotional responses to elearning may be so important in their learning. Methods This study used focus groups as a data collection tool. A purposeful sample of 31 participated. Iterative data gathering and analysis phases employed a constant comparative approach to generate themes firmly grounded in participant experience. Results Key themes that emerged from the data included a sense of injustice, passivity and a feeling of being 'lost at sea'. The actual content of the elearning resource provided important context. Conclusions The identified themes have strong emotional foundations. These responses, interpreted through the lens of achievement emotions, have not previously been described. Appreciation of their importance is of benefit to educators involved in curriculum development or delivery.